2019
DOI: 10.1080/1550428x.2019.1683785
|View full text |Cite
|
Sign up to set email alerts
|

Stories of Sameness and Difference: The Views and Experiences of Children and Adolescents with a trans* Parent

Abstract: Scholarly attention has recently been given to the ways in which gender and parenting identities intersect, yet little is known about how children and adolescents with a trans à parent experience family life and relationships. This article reports data from a qualitative study in the UK based on interviews with 29 children and adolescents aged 5-18, all of whom have at least one parent who is trans Ã. Drawing upon theories of symbolic interactionism, the study investigated children and adolescents' meaning-mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 39 publications
(67 reference statements)
2
25
0
Order By: Relevance
“…However, empirical studies have consistently revealed that many transgender and gender diverse individuals are already parents (Stotzer et al, 2014). Furthermore, post-gender transition parent−child relationships can be positive and child well-being unaffected, especially in the absence of wider family conflict or stigmatization over parental gender transition (see Freedman et al, 2002;White and Ettner, 2007;Hafford-Letchfield et al, 2019;Zadeh et al, 2019). Notably, studies have shown that a considerable number of those engaged in gender transition desire to have children in the future (De Sutter et al, 2002;Wierckx et al, 2012;von Doussa et al, 2015;Riggs et al, 2016;Cipres et al, 2017;Tornello and Bos, 2017;Marinho et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, empirical studies have consistently revealed that many transgender and gender diverse individuals are already parents (Stotzer et al, 2014). Furthermore, post-gender transition parent−child relationships can be positive and child well-being unaffected, especially in the absence of wider family conflict or stigmatization over parental gender transition (see Freedman et al, 2002;White and Ettner, 2007;Hafford-Letchfield et al, 2019;Zadeh et al, 2019). Notably, studies have shown that a considerable number of those engaged in gender transition desire to have children in the future (De Sutter et al, 2002;Wierckx et al, 2012;von Doussa et al, 2015;Riggs et al, 2016;Cipres et al, 2017;Tornello and Bos, 2017;Marinho et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The only qualitative study from an UK child-report data (33 children and adolescents of whom 23 were siblings) found that parental gender identity did not adversely impact upon how children and adolescents perceived their relationship with their parent as they expressed a sense of relational continuity. However, it might be otherwise relevant to their experiences both within and outside of the home with some of them expressing feelings of ambiguous loss, or the need to become responsible or to negotiate family display [ 40 ]. Also, many transgender parents were developing preventative strategies for themselves and their children not to be stigmatized [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of experiences of parenting itself, studies have so far tended to focus on familial experiences during a transition, and how this is negotiated by parents (Hines, 2006;von Doussa et al, 2020), and experienced by children (Veldorale-Griffin, 2014;Zadeh et al, 2019). There has been less research on the experiences of trans and non-binary parents who have identified as trans and/or non-binary since before having their children.…”
Section: Introductionmentioning
confidence: 99%